Local Knowledge of Traditional Medicine and Ethnic Food Duano, Kerinci and Suku Anak Dalam Jambi As a Natural Science Learning Resource - Mustakim, Ardi; Hariyadi, Bambang; Hamidah, Afreni; Falani, Ilham (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this research is to explore the concept of science (biology, physics, and chemistry) in traditional ethnic medicine and food of the Duano, Kerinci, and Suku Anak Dalam Jambi. Methodology: This research examines the concept of science based on traditions and local knowledge as a source of science learning (biology, chemistry, and physics). Type of qualitative research with an ethnographic approach. Data was collected through observation, interviews, FGD, and documentation using Spradley model data analysis. Main Findings: The research found that the Duano Dalam tribe has local traditions and knowledge, such as menorah sunburn, marine ecology, lung, and gulai making. The Kerinci tribe has local knowledge about ethnic medicine and food, including Betemas/Tasapa and surian chili sauce. Meanwhile, the Anak Dalam (SAD) tribe has a tradition of Besale and local knowledge of Batangas and fish Pekasam food. The collection of traditions and local knowledge of each tribe has the potential to become a basis for science concepts in learning. Novelty/Originality of this study: The novelty or originality of the research entitled “Local Knowledge of Traditional Medicine and Ethnic Food of the Duano, Kerinci, and Anak Dalam Tribes as a Natural Science Learning Resource